Eletrobras management program in ergonomics: the pursuit of excellence through maturity levels. - Soares, Marcelo M.; Jacobs, Karen; de Oliveira Bassil Pires, Paulo Roberto; Rezende, Fagner Fagundes (Work)
Ergonomics for Eletrobras arose from the need in having an environment more suitable to the characteristics and circumstances of employees, in compliance with Regulation Standard no. 17 - Ergonomics (NR17) of the Ministry of Labor and Employment. Being a mixed economy company with regionalized anthropometric characteristics of its employees, the study of ergonomic adjustments and improvement of the concept of Ergonomics were and have been of great importance to the company's production environment. These advances have contributed to the development of specific technical criteria for the purchase of furniture and work tools (accessories), apart from their possible effects on the user. Ergonomics has been perceived as a technical-scientific tool, aimed to study labor interactions, new technologies and specific characteristics of the activities performed. To meet these demands a multidisciplinary Ergonomics Committee was created in Eletrobras, and effectively established the Ergonomics Management Program in the company; This program is marked by well-defined phases with great success in making use of these studies for other types of corporate activities and also facilitating the program control and its maturity levels, even at a business level.